Cattle E-Reservation Application Design Trading in PT. Holy Grace Cholis - Anggraeny, Fila (Jurnal Manajemen Informatika Medicom (JMI), 2025)
E-Reservation Application Design Cattle Trading At PT. Holy Grace Cholis. Supervised by Mr. Zainuddin Bey Fananie, M.Sc and Mrs. Arini, MT. The Rahmat Suci Cholis Company was founded in 1996. This company is engaged in beef cattle sales. This company also does marketing directly to the sale of cattle. Currently the system that runs is still manual, has many weaknesses causing the company's performance to be hampered and has not been able to support all the needs of the company. For this reason, in making it easier for companies to place orders, make payments, online and recording sales reports are analyzed and designed a e-reservation application system that can provide the required information by the company. The use of this system is divided into 2 main accesses, namely for the financial admin section and the owner (company owner). Development tools used in this research by using PHP as the language programming and MySQL as the database. Designing and designing systems This e-reservation application uses the Rapid Application Development method (RAD) and Unified Modeling Language (UML) as modeling tools. The final results achieved from the creation of an e-reservation application can be make it easier for companies to place orders and payments through PayPal system, so that it can make it easier for customers to order and online payment through the PayPal system. With this system too can increase company profits